Território e educação no/do campo: um olhar sobre ensino de Geografia na escola do assentamento de reforma agrária Tiradentes/PB - Silva, Lenira Lins da (2024)
Education in/from the countryside is a dimension of the agrarian issue that presents itself complexly in the current scenario. We observed that the rural school plays an important role in the constitution of a territorial identity in which subjects construct their local practices and knowledge, being a space for collective construction. In this way, education in/from the countryside and rural schools are results of the territorialization of the peasantry in the field of public policies. Based on this aspect, we show that this type of teaching is a paradigm in dispute, because, on the one hand, it is part of the demands of peasant peoples, on the other, educational policies are built for and without the peasant people. In this research, we seek to analyze the pedagogical practices developed in the Geography discipline from the perspective of the dimension of the territory and the foundations of education in/from the countryside, at the school in the Tiradentes settlement, Mari – PB. the study starts from a dialectical and phenomenological approach, which allowed us to reflect on the material and symbolic representations in this territory. Strictly speaking, to enter into the discussions we resort to the theoretical assumptions of authors such as Raffestin (1993), Haesbaert (2007), Bauman (2005), Hall (2005) and Almeida (2008), Leite (1999), Saviani (2013), Freire (1984), Caldart (2012), Molina (2014), Arroyo (2013, 2017) and Fernandes (1999). In relation to collecting information, we use different methodological procedures, such as: bibliographic research, documentary research and field research. The latter allowed interviews, observations and workshops aimed at producing mental maps. The results demonstrate that education in/from the countryside is a process under construction at the Tiradentes school and despite the challenges, the unit has been proposing Geography teaching contextualized with the reality and local territorial identity. We clarify that institutional demands and the lack of teacher training influence the development of pedagogical practices correlated with everyday experiences and practices, becoming one of the main imbroglios, however, the school puts itself in struggle and resistance when proposing a differentiated school curriculum , present in the PPP organization. We highlight Geography as a possibility to reflect the dimension of what is experienced in the relationship between school and territory, in which it provides questions, propositions and the exchange of knowledge. Finally, the research carried out identified that at the Tiradentes school, the teaching of Geography is a bridge for students to think about their existence, resistance and remember the process of struggle that originated their territory and the school, however, it still requires a rethink and a reflective look at pedagogical practice in the discipline of Geography, in order to seek to strengthen education in and from the countryside and local territorial identity.